Tissue Distribution of Total Flavonoids Extracts of Drynariae Rhizoma in Young and Old Rats by UPLC–MS/MS Determination. (4th February 2022) - Zhang, Yue; Lei, Xia; Xu, Hongdan; Liu, Guoliang; Wang, Yeqiu; Sun, Huifeng; Geng, Fang; Zhang, Ning
Abstract : Drynariae Rhizoma (Kunze ex Mett.) J. Sm. has been extensively used in China, Japan, and Korea to treat osteoporosis and tonify kidneys. A rapid and validated UPLC-MS/MS method for simultaneous determination of the seven analytes including neoeriocitrin, luteolin-7- O-β -D-glucoside, astragalin, naringin, eriodictyol, naringenin, and kaempferol in rats' various tissues (heart, liver, spleen, lung, kidney, stomach, brain, uterus, ovary, and small intestine) using quercetin as the internal standard (IS) was developed after oral administration of TFDR to rats. Tissues samples were retreated by protein precipitation with methanol. The chromatographic separation was performed using an ACQUITY UPLC™ BEH C18 column (2.1 × 50 mm; 1.7  μ m) at 35°C. The mobile phase consisted of 1% acetic acid in water as the aqueous phase (A) and 100% acetonitrile as the organic phase (B). All analytes and IS were quantified through electrospray ionization in positive ion multiple reaction monitoring (MRM) mode. MS transitions were m/z 597.5 ⟶ 289.2 for neoeriocitrin, m/z 449.1 ⟶ 287.1 for luteolin-7- O-β -D-glucoside, m/z 449.1 ⟶ 287.1 for astragalin, m/z 581.5 ⟶ 273.2 for naringin, m/z 289.2 ⟶ 153.1 for eriodictyol, m/z 273.2 ⟶ 153.1 for naringenin, m/z 287.1 ⟶ 153.1 for kaempferol, and m/z 303.2 ⟶ 153.1 for quercetin (IS). The mean extraction recovery of the seven analytes and IS in tissue samples at three levels of quality control (QC) samples ranged from 82.72% to 118.57%, and the RSD was ≤14.98%. The intraday and interday precision (RSD) were all less than 14.98%, and the accuracy (RE) ranged from −13.96% to 14.96%, which indicated that the present method was not an issue. Tissues distribution showed neoeriocitrin, luteolin-7- O-β -D-glucoside, astragalin, naringin, and naringenin could transfer across the blood-brain barrier, which may form the basis of TFDR entering the brain to play an anti-AD role. Compared with the 8-month-old rats, a higher concentration of naringin was found in the ovaries of the 18-month-old rats; this result indicated that it may regulate the autonomic nervous dysfunction of the cerebrospinal system through the hypothalamus-pituitary-ovary axis, thus playing an anti-AD role, but further research is needed. Naringenin, eriodictyol, and kaempferol have a higher concentration in the liver and kidney; this phenomenon may be related to the traditional Chinese medicine theory that there is a definite relationship between the liver and kidney meridian. These results provide reliable data support for further study of the pharmacological mechanism of TFDR, formulation of drug delivery schemes, and development of new Chinese medicines in the treatment of AD.